Educational Supervision and its Relationship with the School Organization Model in Spain. Theoretical and Regulatory Foundations - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2024)
Educational supervision from the legal, academic and practical fields turns out to be the main function of the inspection that encompasses the other functions of control, advice and evaluation. Supervision is closely linked to school organization since inspectors are assigned reference centers on which they act taking into account their didactic and organizational processes. In this article we are going to refer to the organizational processes, we will leave for another time the relationship of the educational inspection with the didactic aspects, especially with the curriculum. There is a direct relationship between the functions and powers of the inspection with the dynamics of the centers, since they supervise their operation from an organizational and pedagogical point of view; They ensure compliance with the standards in the centers and guide the management teams and the different sectors of the school community, in its powers, the inspection supervises the activities of the centers, examines their documentation and participates in the meetings of the different bodies of the center. The current organizational model, which serves as the basis for inspection action, has been configured over time with the contribution of academic proposals that have been incorporated into the various educational laws. This model still lacks a comprehensive theoretical foundation, although the elements that are important for supervision can be defined: the principles, objectives and purposes; the organizational structure with the powers of the different bodies; institutional plans, especially the educational project; and human resources and teaching materials. The principles of the educational system that condition the organizational model and inspire supervisory action are: school participation, quality, autonomy, evaluation, equity, inclusion and education in values. Of all of them, those that most define and influence the organizational model are analyzed: school participation; quality and improvement, along with equity; and autonomy with educational leadership. For each of these principles, the most significant characteristics that are essential to keep in mind in supervisory action are defined and the reflections made, by inspectors are described in relation on the subject. It concludes with some final considerations and recommendations.